2019
DOI: 10.1021/acs.jafc.9b02326
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics and Mechanisms for Photodegradation of Nitrated Polycyclic Aromatic Hydrocarbons on Lettuce Leaf Surfaces: An In Vivo Study

Abstract: Insights into the environmental fates of nitrated polycyclic aromatic hydrocarbons (NPAHs) in edible vegetables are of great significance for better evaluating human exposure to NPAHs through the dietary pathway. In this work, a fluorescence quenching method using graphene quantum dots as a fluorescent probe was first applied for the in vivo determination of 9-nitroanthracene (9-NAnt) and 1-nitropyrene (1-NPyr) adsorbed on the leaf surfaces of living lettuce (Lactuca sativa L.) seedlings. Moreover, the photoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This evidence can be mutually supported by our previous investigation of 89 milk samples in which the parent PAHs of 9-FO and ATQ (fluorene and anthracene) were also detected in all samples. Actually, it was reported that ATQ may occur in light or thermal processes during food processing and storage. Therefore, it is reasonably assumed that these OPAHs can be produced by the oxidization of parent PAHs during thermal processing. ATQ has been classified as a 2B carcinogen by the International Agency for Research on Cancer .…”
Section: Resultsmentioning
confidence: 99%
“…This evidence can be mutually supported by our previous investigation of 89 milk samples in which the parent PAHs of 9-FO and ATQ (fluorene and anthracene) were also detected in all samples. Actually, it was reported that ATQ may occur in light or thermal processes during food processing and storage. Therefore, it is reasonably assumed that these OPAHs can be produced by the oxidization of parent PAHs during thermal processing. ATQ has been classified as a 2B carcinogen by the International Agency for Research on Cancer .…”
Section: Resultsmentioning
confidence: 99%
“…Although there is compelling evidence for the presence of exogenous substances onto plant leaves, information on their multiphase reactivity is scarce and biased toward anthropogenic compounds. To the best of our knowledge, leaf-surface photodegradation of pesticides is the only process that has been investigated in detail (reviewed by Sleiman et al and others , )although primarily in laboratory settings using model surfaces or reconstructed cuticles. ,, Some work has also been performed on the photodegradation of PAHs and their oxidation products on and within leaf cuticles, while other studies investigated HNO 3 /nitrate photolysis on leaves of various plants. , On the contrary, the reactivity of anthropogenic SVOCs adsorbed on leaves with other gas-phase oxidants has received considerably less attention . An early investigation reported the oxidation of parathion (a pesticide) adsorbed onto lemon tree leaves in the presence of ozone and “foliar dust” (soil organic matter particles) .…”
Section: Chemicals From the Environmentmentioning
confidence: 99%
“…Overall, photodegradation obeys pseudo-first-order kinetics, with reaction rate constants that change considerably (but not predictably) based on chemistry, surface coverage, and micromorphology of the reaction substrate, as well as co-occurrence of other substances (e.g., Figure ). ,, Formulation ingredients (e.g., surfactants) and co-occurring volatile and semivolatile metabolites can further influence surface photolysis by acting as photosensitizers or quenchers of reactive species, stabilizing radical intermediates, screening light, or a combination of these processes. ,,, By modifying the leaf’s wettability, surfactants can also influence shape, density, and crystallinity of the active ingredient’s residue, with impacts on its photochemical stability. , Variation in epicuticular wax chemistry, thickness, and morphology impact photodegradation in a similar manner . Wax components may act as photosensitizers or quenchers of reactive species and actively participate in reactions to form “bond residues”, whereas the presence of specific microstructures modifies light transmission and water spreading. ,, SVOC solubility in epicuticular waxes can also impact half-lives, as compounds buried within the cuticle are less susceptible to photodegradation than less lipophilic molecules sitting on its surface .…”
Section: Chemicals From the Environmentmentioning
confidence: 99%
“… Deposition of PAHs and their retention on leaf surfaces make them more susceptible to photodegradation. However, the photodegradation rate can be highly influenced by various factors, including PAHs location on leaves, their photochemical behavior and structure, as well as the nature of the substrate. , Once the PAHs penetrate the epidermal cell wall or cytoplasm, they become protected from photodegradation, but more susceptible to cell metabolism . Investigations into the environmental behavior of PAHs on different types of leaves/needles, including those from mangrove, spruce, oak, or pine, have demonstrated their significant involvement in the photolysis of PAHs on the leaf surface, thereby influencing the environmental fate of PAHs. ,, Chen et al studied the fluorene (FLU) photolysis processes in three different mangrove leaves and observed variations in photolysis rates among three of them.…”
Section: Uptake and Translocation And The Fate Of Pahs In Plantsmentioning
confidence: 99%